2011
DOI: 10.1128/jvi.00674-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Deletion Mutant Respiratory Syncytial Virus Strains Lacking Most of the G Protein in Immunocompromised Children with Pneumonia in South Africa

Abstract: Respiratory syncytial virus (RSV)G

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Similarly, while a number of truncated G proteins have been observed in RSV-B in vivo (29), we are unaware of reports of truncated G proteins in RSV-A in vivo. Studies of RSV escape from antibody-mediated selection have shown that premature stop codons in the C-terminal region can lead to antibody escape in cell culture (11).…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, while a number of truncated G proteins have been observed in RSV-B in vivo (29), we are unaware of reports of truncated G proteins in RSV-A in vivo. Studies of RSV escape from antibody-mediated selection have shown that premature stop codons in the C-terminal region can lead to antibody escape in cell culture (11).…”
Section: Resultsmentioning
confidence: 94%
“…A live-attenuated RSV vaccine candidate lacking most of the SH and G genes due to spontaneous deletions during passage in vitro appeared to be competent for replication in children, although it was highly restricted (Karron et al 1997a). RSV isolates have been found, from infants exposed to or infected with human immunodeficiency virus, with deletions spanning most of the G ectodomain, indicating that loss of most of G can occur in nature in some situations (Venter et al 2011). Thus, G is a malleable, variable protein that is absolutely not essential for replication.…”
Section: Proteinsmentioning
confidence: 99%
“…Virus passaged in vitro occasionally can acquire inserts of one (usually) or more U residues (negative sense) into the U tract at the end of GE signals or into untranslated sequence. Spontaneous deletion of the G and SH genes has been noted in vitro, and deletion of most of the G gene has been noted in vivo (Venter et al 2011). Two different spontaneous intragenic duplications of a segment of the G gene have been documented in nature (Eshaghi et al 2012), and in one case the resulting virus has spread worldwide and continued to evolve.…”
Section: Spontaneous Mutationsmentioning
confidence: 99%
“…Many studies have confirmed that the premature stop codons affect the antigenicity of the G protein without modifying its entire function or its role in infectivity. Truncated genes have been described in both A subtypes [16] and with greater frequency in B subtype viruses [25], evidencing that this mechanism is important for generating genetic and antigenic diversity [4,26] and contributing to shaping the immune response in a defined population when changing the selective pressure on each subtype. For example, this stop codon apparition was used by the influenza A virus, which modified the length of NS1 without affecting its function [27] in a similar way to that used by RSV.…”
Section: Discussionmentioning
confidence: 99%